Evaluation of Herbicide Programs for Use in a 2, 4-D–Resistant Soybean Technology for Control of Glyphosate-Resistant Palmer Amaranth (Amaranthus palmeri). (June 2016) - Miller, M. Ryan; Norsworthy, Jason K.
Abstract : Two separate field experiments were conducted over a 2-yr period in Fayetteville, AR, during 2012 and 2013 to (1) evaluate POST herbicide programs utilizing a premixture of dimethylamine (DMA) salt of glyphosate + choline salt of 2, 4-D in a soybean line resistant to 2, 4-D, glyphosate, and glufosinate and (2) determine efficacy of herbicide programs that begin with PRE residual herbicides followed by POST applications of 2, 4-D choline + glyphosate DMA on glyphosate-resistant Palmer amaranth. In the first experiment, POST applications alone that incorporated the use of residual herbicides with the glyphosate + 2, 4-D premixture provided 93 to 99% control of Palmer amaranth at the end of the season. In the second experiment, the use of flumioxazin, flumioxazin + chlorimuron methyl, S- metolachlor + fomesafen, or sulfentrazone + chloransulam applied PRE provided 94 to 98% early-season Palmer amaranth control. Early-season control helped maintain a high level of Palmer amaranth control throughout the growing season, in turn resulting in fewer reproductive Palmer amaranth plants present at soybean harvest compared to most other treatments. Although no differences in soybean yield were observed among treated plots, it was evident that herbicide programs should begin with PRE residual herbicides followed by POST applications of glyphosate + 2, 4-D mixed with residual herbicides to minimize late-season escapes and reduce the likelihood of contributions to the soil seedbank. Dependent upon management decisions, the best stewardship of this technology will likely rely on the use multiple effective mechanisms of action incorporated into a fully integrated weed management system.